Temperature dependence and magnetocrystalline anisotropy studies of self-assembled L1(0)-Fe55Pt45 ferromagnetic nanocrystals - Varanda, L. C.; Jafelicci, M.; Imaizumi, M. (American Institute of Physics (AIP), 2007)
Temperature dependence and uniaxial magnetocrystalline anisotropy properties of the chemically synthesized 4 nm L1(0)-Fe55Pt45 nanoparticle assembly by a modified polyol route are reported. As-prepared nanoparticles are superparamagnetic presenting fcc structure, and annealing at 550 degrees C converts the assembly into ferromagnetic nanocrystals with large coercivity (H-C>1 T) in an L1(0) phase. Magnetic measurements showed an increasing in the ferromagnetically ordered fraction of the nanoparticles with the annealing temperature increases, and the remanence ratio, S=M-R/M-S congruent to 0.76, suggests an (111) textured film. A monotonic increase of the blocking temperature T-B, the uniaxial magnetocrystalline anisotropy constant K-U, and the coercivity H-C with increasing annealing temperature was observed. Magnetic parameters indicate an enhancement in the magnetic properties due to the improved Fe55Pt45 phase stabilizing, and the room-temperature stability parameter of 67, which indicates that the magnetization should be stable for more than ten years, makes this material suitable for ultrahigh-density magnetic recording application.(c) 2007 American Institute of Physics.